The Role of Cloud Processing for the Ice Nucleating Ability of Organic Aerosol and Coal Fly Ash Particles. Issue 10 (19th May 2021) - Kilchhofer, Kevin; Mahrt, Fabian; Kanji, Zamin A.
Abstract: Ice nucleating particles are a minor fraction of tropospheric aerosol, yet they play a key role for cloud microphysical processes. One poorly understood process is the impact of atmospheric aging of aerosol particles on ice nucleation. Here we study the impact of cloud processing on the ice nucleation abilities of two physicochemically different aerosol particles by taking two model systems for atmospheric organic aerosol (OA), as well as coal fly ash (CFA) particles representing an inorganic aerosol type. The ice nucleation activity of the unprocessed particles is compared to aerosol particles that are first exposed to conditions mimicking trajectories though cirrus clouds (CC) and mixed‐phase clouds (MPC) prior to testing their ice nucleation activity at temperatures below 243 K. We observed that unprocessed OA do not exhibit heterogeneous ice nucleation, requiring homogeneous freezing conditions of solution droplets to form ice. However, after CC processing raffinose particles showed heterogeneous ice nucleation activity at 218 K and a water saturation ratio of 0.68–0.82, reaching activated fractions of up to 0.3. This enhancement compared to unprocessed raffinose particles results from an increase in particle viscosity upon CC processing. We also present new results of unprocessed CFA particles exhibiting strong heterogeneous ice nucleation activity at temperatures below 235 K in the deposition and/or pore condensation and freezing mode. In contrast to the OA, the CFA show a decrease in ice nucleation activity after both MPC and CC processing. Furthermore, cloud processing and generating CFA particles from aqueous suspensions do not have the same effect on their ice nucleation ability. Key Points: Cloud processing can increase organic particle viscosity enhancing their ice nucleation activity Coal fly ash particles show a decreased ice nucleation ability after cloud processing Aerosol generation methods impact the observed ice nucleation abilities of coal fly ash particles